2013
DOI: 10.7314/apjcp.2013.14.6.3719
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between RASSF1A Promoter Methylation and NSCLC: A Meta-analysis of Published Data

Abstract: Background: RASSF1A has been reported to be a candidate tumor suppressor in non-small cell lung cancer (NSCLC). However, the association between RASSF1A promoter methylation and NSCLC remains unclear, particularly in regarding links to clinicopathologic features. Methods: Eligible studies were identified through searching PubMed, EMBASE, Cochrane Library and China National Knowledge Infrastructure (CNKI) databases. Studies were pooled and odds ratios (ORs) with corresponding confidence intervals (CIs) were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Methylation of the RASSF1A promoter is described as an early and frequent event in tumorigenesis, thus RASSF1A can serve as a useful diagnostic marker in cancer screening (Dammann et al, 2000;Dammann et al, 2001;Liu WJ et al, 2013), including ovarian cancer (Agathanggelous et al, 2001;Yoon et al, 2001;Rathi et al, 2002;Ibanez et al, 2004;Makarla et al, 2005;Choi et al, 2006;Ma et al, 2009;BonDurant et al, 2011;Bhagat et al, 2012).…”
Section: Aberrant Methylation Of Rassf2a In Tumors and Plasma Of Patimentioning
confidence: 99%
“…Methylation of the RASSF1A promoter is described as an early and frequent event in tumorigenesis, thus RASSF1A can serve as a useful diagnostic marker in cancer screening (Dammann et al, 2000;Dammann et al, 2001;Liu WJ et al, 2013), including ovarian cancer (Agathanggelous et al, 2001;Yoon et al, 2001;Rathi et al, 2002;Ibanez et al, 2004;Makarla et al, 2005;Choi et al, 2006;Ma et al, 2009;BonDurant et al, 2011;Bhagat et al, 2012).…”
Section: Aberrant Methylation Of Rassf2a In Tumors and Plasma Of Patimentioning
confidence: 99%
“…It has been reported that the RASSF1A gene is frequently inactivated in lung cancer by the de novo methylation of CpG islands in the promoter region Honorio et al, 2003;Grote et al, 2006). RASSF1A promoter methylation might play a pivotal role in the development of Lung cancer (Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…RASSF1A is a cell cycle-related tumor suppressor protein that that decreases colony formation, suppresses anchorage-independent growth, and dramatically reduces tumorgenicity in vivo. Previous studies have reported the involvement of RASSF1A promoter methylation in several cancers, including prostate (Ge et al, 2014), Ovarian (Vo et al, 2013), lung cancer (Liu et al, 2013). It has been reported that the RASSF1A gene is frequently inactivated in primary lung cancers by the de novo methylation of CpG islands in the promoter region Tomizawa et al, 2002).…”
Section: Association Between Cigarette Smoking and Rassf1a Gene Promomentioning
confidence: 99%
“…Association between RASSF1A Ala133Ser Polymorphism and Cancer Susceptibility: A Meta-Analysis Involving 8,892 Subjects Suleyman Bayram may be asscoated with cancer development (Liu et al, 2013;Vo et al, 2013).…”
Section: Research Articlementioning
confidence: 99%